Trauma Informed Care and Social Work Education: A Case Study - Kawam, Elisa (Advances in Social Sciences Research Journal, 2014)
This paper provides a brief description and history of trauma in the social sciences alongside an introduction to trauma informed care in social work education. This paper promotes the understanding that trauma assessment and treatment are a key component to the future of social work education and practice. As a result of a recent teaching experience, a framework for conceptualizing, treating, and supervising trauma related disorders within an educational context was developed. This paper utilizes that unique teaching experience where a graduate course on trauma informed care proved challenging yet profound to the existing methods typically sanctioned for university and college settings. These challenges and the corresponding opportunities associated with trauma work are discussed. Practical and ethical implications of a social work model of trauma-focused are outlined. A case example, employing several students’ experiences, is presented. Suggestions for additional study are outlined.